Estudo de tipologias do morar para terceira idade em edifício de apartamentos - Bernardo, Maria Alva (2005)
The research bring up the discussion about the need of rethinking the living, appropriate to all life phases and not only that produced for the adult-man-pattern, as it is verified nowadays in the practices of the estate market. It is fact that the called third age people is receiving more attention in the part of the researchers of different areas, mainly with the increase in the number of senior people due the increase of life expectation and decrease of the birth rate, but there are still few referring studies to the adaptation of architectural spaces, especially in buildings of apartments. The desire of most people, to live more and more, can result in an extended time of life, marked by incapacities and dependence. The challenge is to get a larger more life with quality. In that sense, the home place, symbol and representation of the social identity of each one, needs to be thought from way to adapt all the stages of the life. This research presents suggestions of a theoretical conceptual model, through the analysis of the physical space of buildings of apartments built/projected in Vitória/ES, tracing a parallel among the ones that are produced/offered for the market and the seniors' needs that request dimensionally and appropriate ambients, specifics for them to in such a way to make them safe and comfortable, allowing them larger independence through the projected spaces by using materials and appropriate accessories, and looking for to assist the functional and physical limitations of the third age. Two apartments were analyzed, being one with the typology of the decade of 1970 and another of the year of 2005, with program of 03 rooms with suite, social bathroom, living room, cooking and service areas. It was established a comparative situation among the current production and considered ideal in terms of adaptation of the physical space for the third age. Through it, it can be proven that with a minimum area increase is possible to produce apartments projected based in the universal drawing.